Interaksi Sosial dalam Praktik Keagamaan Umat Buddha: Systematic Literature Review (SLR) - Novita Novita; Partono Partono; Kabri Kabri; Riasih Riasih (Indo Publishing, 2026)
This review synthesizes research on social interaction in Buddhist religious practices, focusing on community gatherings, rituals, and meditation groups to address gaps in understanding their roles in social cohesion, cultural identity, and community dynamics. The review aims to evaluate the social functions of rituals and communal gatherings, compare meditation groups as social sites, identify mechanisms that foster cohesion and intercultural harmony, analyze the role of leadership, and contrast traditional and contemporary practices. A systematic analysis of qualitative, quantitative, and mixed-method studies across diverse Buddhist traditions and geographical contexts was conducted, with particular emphasis on ethnographic and survey data from Asia, North America, and diaspora communities. The findings reveal that Buddhist rituals and meditation groups significantly enhance social integration, identity formation, and intercultural tolerance, while also adapting innovatively to urbanization and digital mediation. Spiritual leaders emerge as key mediators of social networks and cultural values, although issues of power dynamics and inclusivity warrant further scrutiny. Contemporary transformations are reshaping social practices but remain insufficiently examined through comprehensive critical evaluation. Collectively, these findings demonstrate the multifaceted social functions of Buddhist practices as dynamic sites of community resilience and cultural negotiation. This review underscores the need for integrative comparative research to deepen theoretical frameworks and to inform policy and community engagement in Buddhist studies and the broader study of religion